Potential Biological Roles of Exosomal Long Non-Coding RNAs in Gastrointestinal Cancer - Kang, Fanhua; Jiang, Feng; Ouyang, Lingzi; Wu, Shangjun; Fu, Chencheng; Liu, Ying; Li, Zhilan; Tian, Yu; Cao, Xiaolan; Wang, Xiaoping; He, Qingchun (Frontiers in Cell and Developmental Biology, 2022)
Exosomes, a kind of extracellular vesicles (EVs) secreted by almost all cells, contain many cellular constituents, such as nucleic acids, lipids, metabolites, etc. And exosomes play important roles in intercellular communication, involving in the development and treatment of gastrointestinal cancer. Long noncoding RNA (LncRNAs) have been confirmed to participate in a variety of biological functions, such as cell metastasis, tumorigenesis and therapeutic response. In this review, we mainly focused on the emerging roles and underlying molecular mechanisms of exosomal-derived lncRNAs in gastrointestinal cancer in recent years. We also discussed the biological functions of exosomal lncRNAs in the pathogenesis and therapeutic response of gastrointestinal cancer.